IBTIDAIYAH MADRASAH (MI) AND INTEGRATED ISLAMIC PRIMARY SCHOOL (SDIT) REQUEST OF ISLAMIC EDUCATION AND INTEGRAL PARADIGM IN THE SISDIKNAS LAW NO. 20 OF 2003 - Nurhadi Nurhadi (TA'LIM : Jurnal Studi Pendidikan Islam, 2019)
The emergence and existence of the madrasa cannot be separated from the Islamic reform movement which was initiated by the efforts of a number of religious intellectuals who were later developed by Islamic organizations in Java, Sumatra and Kalimantan. Educational institutions currently have three models that have developed in Indonesia, namely schools (general) as mentioned above, madrasas (religions) as well as those mentioned above, and pesantren. The three according to some thinkers cannot realize the education objectives of the National Education System. The author Analsis stated the substantive goals of national education in the National Education System Act No. 20 of 2003 is Islamization and Integration of Islamic education. By combining the two paradigms of Islamic education is likely to be realized with the actual purpose of education. There are four factors that SDIT is very substantive with national education goals in the National Education System Act No. 20 of 2003, which is an Islamization and Integralism of Islamic education, in accordance with the purpose of education in the Act Chapter II Article 3, namely: "To develop the potential of students to become human beings who believe and fear the Almighty God, have a noble, healthy character, knowledge, skillful, creative, independent, and become a democratic and responsible citizen ". Religion with its legality and formality, both knowledge and administration, and both Islamic education institutions are very high and equal, equal to equivalent general education, namely elementary school (SD). This can be seen from the recognition of MI and its integral curriculum both general curriculum and religion, according to its characteristic that MI school-based madrasas (imtaq and science and technology) and SDIT are religion-based schools (science and technology and imtaq).